2008
DOI: 10.1038/ejhg.2008.195
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic 22q13 deletions: evidence for concurrent mosaic segmental isodisomy and gene conversion

Abstract: Although 22q terminal deletions are well documented, very few patients with mosaicism have been reported. We describe two new cases with mosaic 22q13.2-qter deletion, detected by karyotype analysis, showing the neurological phenotype of 22q13.3 deletion syndrome. Case 1 represents an exceptional case of mosaicism for maternal 22q13.2-qter deletion (45% of cells) and 22q13.2-qter paternal segmental isodisomy (55% of cells). This complex situation was suspected because cytogenetic, FISH and array-CGH analyses sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Although clearly indicating a RABL2B deficiency, the value is different from the expected ratio of 0.5. Whether this reflects a mosaic 22q13 deletion known to occur (Bonaglia et al, 2009) remains to be elucidated. Data are summarized in Table 1.…”
Section: Modified Pyrosequencing Protocol For High-throughput Screeningmentioning
confidence: 96%
“…Although clearly indicating a RABL2B deficiency, the value is different from the expected ratio of 0.5. Whether this reflects a mosaic 22q13 deletion known to occur (Bonaglia et al, 2009) remains to be elucidated. Data are summarized in Table 1.…”
Section: Modified Pyrosequencing Protocol For High-throughput Screeningmentioning
confidence: 96%
“…PMS is typically caused by the loss of the distal segment of the long arm of chromosome 22, as the consequence of terminal or interstitial (subtelomeric) deletions, balanced or unbalanced translocations, ring chromosomes (the chromosome arms are fused together to form a ring), and mosaicisms of these anomalies (Bonaglia et al, 2009; Bonaglia et al, 2011; Dhar et al, 2010; Jeffries et al, 2005; Luciani et al, 2003; Phelan and McDermid, 2012; Sarasua et al, 2014a; Soorya et al, 2013; Wilson et al, 2003). Microscopically visible rearrangements, including large deletions, translocations and ring chromosomes, can be detected with G-banding karyotyping (Bonaglia et al, 2011; Soorya et al, 2013), while cryptic translocations can be revealed using fluorescence in situ hybridization (FISH) (Bonaglia et al, 2001).…”
Section: The Etiology Underlying Phelan Mcdermid Syndromementioning
confidence: 99%
“…Simple terminal deletions account for approximately 75% of PMS cases 10. The other cases have been comprised of translocations in the 22q13 region,2 11–13 ring chromosome 221 2 14–16 and mosaics 17 18…”
Section: Introductionmentioning
confidence: 99%